2023
DOI: 10.18231/j.ijmr.2022.049
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in HIV patients: A case report for timely diagnosis and prompt intervention

Abstract: Cryptosporidium is one of the major causes of diarrhea in HIV-positive patients. Infection is related to the ingestion of oocyst-contaminated drinking water or food. In HIV infected individuals, this infection could have a higher mortality and vary in clinical manifestation. We report a case of cryptosporidiosis in a recently detected HIV patient who was suffering from intermittent diarrhea for last 2 months. Stool samples were collected and examined by modified Kinyoun’s acid fast staining. On microscopy of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…12 At present, Nitazoxanide, a thiazolide antiprotozoal, is a Food and Drug Administration (FDA) approved treatment that reduces the load of parasites and is recommended as first line drug for Cryptosporidiosis in immunocompetent individuals. 6,7 Therapy still remains a challenge for the immunocompromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 At present, Nitazoxanide, a thiazolide antiprotozoal, is a Food and Drug Administration (FDA) approved treatment that reduces the load of parasites and is recommended as first line drug for Cryptosporidiosis in immunocompetent individuals. 6,7 Therapy still remains a challenge for the immunocompromised.…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies have shown that the median infectious dose is just 132 oocysts and infected cases can excrete up to 10 8 oocysts per day. 2,6 Enteric parasitic infestation is a major public health problem especially in the tropical regions of the developing countries. Cryptosporidium spp can cause severe diarrhea and malnutrition leading to fatal outcomes in the immunocompromised.…”
Section: Introductionmentioning
confidence: 99%